Nitrogen Fertilization Boosts Maize Grain Yield, Forage Quality, and Estimated Meat Production in Maize–Forage Intercropping - Gilli, Bruno R. [UNESP]; Grassmann, Camila S. [UNESP]; Mariano, Eduardo; Rosolem, Ciro A. [UNESP] (MDPI, 2023)
Crop–livestock integrated systems such as intercropping and crop rotation have been critical for sustainable agriculture, promoting land use intensification throughout the year. The success of these systems under no-till depends on numerous factors, and the choice of forage grass is paramount. In this study, maize grain yield, forage dry matter yield, bromatological quality, and estimated meat production were assessed in a field experiment where maize (Zea mays L.) was intercropped with Guinea grass (Megathyrsus maximus cv. Tanzania) and palisade grass (Urochloa brizantha cv Marandu) under N rates from 0 to 270 kg ha−1. Nitrogen fertilization resulted in the highest forage dry matter yield, on average, 2.9-fold higher than the N-unfertilized treatments. The highest maize grain yield was obtained with 270 kg ha−1 of N, 48% higher than all other treatments. Guinea grass intercropped with maize and fertilized with 270 kg ha−1 of N resulted in an estimated meat production 27% higher than palisade grass at the same N rate. However, at the final cut, Guinea grass fertilized with 270 kg ha−1 of N led to the highest neutral detergent fiber, acid detergent fiber, and cellulose. While palisade grass seems to impose lower competition with maize, Guinea grass increases estimated meat production.
Keywords: forage production; integrated agricultural system; Megathyrsus maximus; Urochloa brizantha; Zea maysL